Learning demands of diabetes self-management: a qualitative study with people who use insulin - Carla Assad Lemos; Ana Maria Rosa Freato Gonçalves; Elisabeth Meloni Vieira; Leonardo Régis Leira Pereira (Universidade de São Paulo, 2024)
Objective: to understand the experiences with diabetes mellitus management of people who use insulin, in order to identify possible factors that may influence adherence to self-care and thus define their learning demands for diabetes self-management. Method: this is a qualitative study carried out using individual semi-structured interviews online. The interviews were recorded, transcribed and evaluated using Atlas.ti® software by means of Thematic Content Analysis, using the Health Beliefs Model as a theoretical framework. Results: 11 people living with diabetes and using insulin took part in the study. Four categories were identified: understanding diabetes, how to deal with diabetes, difficulties related to insulin use and emotional adaptation. Conclusion: the perception of the severity of the disease, its complications and the benefits of adhering to treatment positively influences adherence to self-care behaviors. Although the study participants have lived with diabetes for many years, they are not exempt from difficulties related to insulin use and disease management, reinforcing the importance of continuing health education. In this sense, the findings of this study guide important educational themes to be worked on by health professionals to promote autonomy in diabetes self-management.